Vacuum pyrolysis incorporating microwave heating and base mixture modification: An integrated approach to transform biowaste into eco-friendly bioenergy products. (July 2020) - Ge, Shengbo; Foong, Shin Ying; Ma, Nyuk Ling; Liew, Rock Keey; Wan Mahari, Wan Adibah; Xia, Changlei; Yek, Peter Nai Yuh; Peng, Wanxi; Nam, Wai Lun; Lim, Xin Yi; Liew, Chin Mei; Chong, Chi Cheng; et al.
Abstract: The escalating consumption of fossil fuels and dumping of palm kernel shells (PKS) drives biofuel production to improve supply and waste disposal. To convert PKS into modified biochar (MBC) value-added solid fuel, we use microwave vacuum pyrolysis accompanied by sodium-potassium hydroxide mixture modification. First, PKS underwent microwave vacuum pyrolysis to produce biochar, and then it was chemically activated using sodium-potassium hydroxide mixture. The MBC surface morphology, porous characteristics, proximate content, and energy properties depended on microwave irradiation period and power. High yields (79 ± 1.5 wt%) were recorded at microwave power 700 W and irradiation period of 10 min, giving a high BET surface area (1320 m 2 /g) and pore volume (0.70 cm 3 /g). The MBC had acceptable low content of ash, nitrogen, and no sulphur, demonstrating its potential as an environmental friendly fuel to replace conventional coal in combustion. The MBC shows high energy yield (≤90.5%), fuel ratio (≤26.47), and heating value (≤28.69 MJ/kg) comparable to conventional fuels, thus showing desirable solid fuel properties. Energy balance analysis shows positive energy ratio of up to 10 and net energy output of up to 24.47 MJ/kg, recovering a product with a higher energy content compared to electrical power input for the pyrolysis operation. These findings demonstrate the exceptional potential of the MBC produced by this innovative approach for bioenergy generation that per se will reduce the emissions of greenhouse gases and thereby reducing global warming and climate change. Graphical abstract: Image 1 Highlights: Microwave vacuum pyrolysis with hydroxide base mixture produces modified biochar. Up to 79 wt% of the modified biochar have high carbon and fixed carbon. The modified biochar shows high calorific value, energy yield, and fuel ratio. The modified biochar is eco-friendly having low ash, nitrogen, no sulphur content. The energy output from this pyrolysis approach is up to 24.47 MJ/kg.